Dictionary of computing. - Collin, S. M. H. 1966- . (London A&C Black, 2010)
Provides definitions of hardware, software, programming language, network, and application terminology along with contextual information and supplies hardware, ASCII coding and programming examples.
Previous ed. entered under: S.M.H. Collin. London : Bloomsbury, 2004.
Keywords: Computers -- Dictionaries